2021
DOI: 10.1210/clinem/dgab103
|View full text |Cite
|
Sign up to set email alerts
|

PREVENT: A Randomized, Placebo-controlled Crossover Trial of Avexitide for Treatment of Postbariatric Hypoglycemia

Abstract: Context Post-bariatric hypoglycemia (PBH), characterized by enteroinsular axis overstimulation and hyperinsulinemic hypoglycemia, is a complication of bariatric surgery for which there is no approved therapy. Objective To evaluate efficacy and safety of avexitide [exendin(9-39)], a GLP-1 antagonist, for treatment of PBH. Design Phase II, randomized, placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…In contrast, pasireotide often causes continuous hyperglycemia [514,515]. More recent drug treatments for post-bariatric hypoglycemia are canagliflozin [516], avexitide [517], or a Closed-Loop Glucagon System [518]. Endoscopic techniques may reduce the diameter of the anastomotic mouth and help to maintain weight reduction.…”
Section: Recommendation 94mentioning
confidence: 99%
“…In contrast, pasireotide often causes continuous hyperglycemia [514,515]. More recent drug treatments for post-bariatric hypoglycemia are canagliflozin [516], avexitide [517], or a Closed-Loop Glucagon System [518]. Endoscopic techniques may reduce the diameter of the anastomotic mouth and help to maintain weight reduction.…”
Section: Recommendation 94mentioning
confidence: 99%
“…Available medical treatments for HI are currently limited, insufficiently effective, and associated with significant side effects ( 22 24 ); by targeting the underlying pathophysiology, exendin-(9-39) offers potential therapeutic advantages over currently available therapies for HI, particularly for cases due to inactivating K ATP channel mutations that are not responsive to diazoxide. Furthermore, exendin-(9-39) has been well tolerated without significant treatment-related side effects in children with HI and also in adults with post–bariatric surgery hypoglycemia ( 25 , 26 ). Exendin-(9-39) has been granted breakthrough therapy designation for the treatment of HI ( 27 ), and future studies to evaluate efficacy and safety of multiple dose regimens are under development.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of hypoglycemia measured by continuous glucose monitor and number of hypoglycemic events were decreased in the subjects treated with exendin-(9-39). There was a statistically significant increase in glucose nadir and decrease in insulin peak during the mixed meal tolerance test ( 49 ). Another study found a reduction in symptomatic hypoglycemic events, as well as decreased insulin peak and increased glucose nadir during oral glucose tolerance tests in subjects receiving exendin-(9-39) ( 50 ).…”
Section: Role Of Glp-1 In Hyperinsulinemic Hypoglycemia Secondary To ...mentioning
confidence: 99%